A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Charlie Martin (J. Carrol Naish) celebrating his new partnership with Arturo de Cordova (Joe Morales). Lolita Sierra (Dorothy Lamour) forces Morales to admit that the boat has sunk in Paramount Pictures 1945 production of 'A Medal for Benny.' According to caption, the production company was giving Lamour and de Cordova an opportunity to show their talents with this movie.